Furoic acid-doped-over-oxidized poly (3, 4-ethylenedioxythiophene)-based electrochemical sensor for selective, sensitive and concurrent quantification of paracetamol, codeine phosphate and caffeine in pharmaceutical formulation - Kocyigit, Nilufer; Dinc-Zor, Sule; Yagci, Ozlem; Arvas, Melih Besir (SPRINGER HEIDELBERG, 2025)
Herein, furoic acid-doped-over-oxidized poly(3,4-ethylenedioxythiophene)-modified pencil graphite electrode (furoic acid-doped-oo-PEDOT/PGE) was firstly prepared and then employed for the simultaneous and sensitive electrochemical determination of paracetamol (PAR), codeine phosphate (COD-P) and caffeine (CAF). Distinctive functional properties of the furoic acid-doped-oo-PEDOT electrode exhibit selective, sensitive and rapid analysis of the target drugs. The electrochemical performance of the prepared sensor electrode was investigated using differential pulse voltammetry (DPV), cyclic voltammetry (CV) and electrochemical impedance spectroscopy (EIS) methods. The calibration curves of the drugs show excellent linearity over a concentration ranges: 0.5-100 mu mol L-1 for PAR, 0.75-100 mu mol L-1 for COD-P and 25-5000 mu mol L-1 for CAF and limit of detection (LOD) values of 0.075, 0.36 and 9.41 mu mol L-1for the analytes, respectively. Finally, the fabricated sensor was successively used for the simultaneous determination of PAR, COD-P, and CAF in commercial pharmaceutical samples and displayed appreciable recoveries.Graphical abstractElectrochemical Sensor Design for Paracetamol, Codeine phosphate and Caffeine
Keywords: Electrochemical sensor; OO-PEDOT; Furoic acid; Paracetamol; Codeine phosphate; Caffeine; ACETAMINOPHEN; OXIDE; Materials Science